1978
DOI: 10.1177/000331977802900406
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Changes Induced by Prolonged NaCl and DOCA Administration in Spontaneously Hypertensive Rats

Abstract: The results of this study demonstrate that the spontaneously hypertensive rat is sensitive to salt excess. The hypertensinogenic effect of salt was mediated through elevation of peripheral vascular resistance. The addition of DOCA aggravated the hypertension, mainly be elevating the cardiac output without appreciably decreasing peripheral vascular resistance. SHR'S EXPOSED TO 1% NaCl consumed more fluids and excreted more sodium and urine than control rats. Those exposed to 1% NaCl and DOCA had higher fluid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 22 publications
(2 reference statements)
3
16
0
Order By: Relevance
“…Interestingly, whereas we and others have observed small but significant increases in plasma OSM or Na levels in the DOCA-salt animals compared with Sham-salt controls, [7][8][9][10] in the current study, OSM and Na were insignificantly increased by Ͻ2%. Earlier studies have also failed to detect significant increases in plasma Na concentration (eg, see References [22][23][24] ). Yet, despite the small magnitude, our data clearly suggest that these extremely small, at times undetectable, elevations in OSM are sufficient to produce hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, whereas we and others have observed small but significant increases in plasma OSM or Na levels in the DOCA-salt animals compared with Sham-salt controls, [7][8][9][10] in the current study, OSM and Na were insignificantly increased by Ͻ2%. Earlier studies have also failed to detect significant increases in plasma Na concentration (eg, see References [22][23][24] ). Yet, despite the small magnitude, our data clearly suggest that these extremely small, at times undetectable, elevations in OSM are sufficient to produce hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Although some investigators have believed that the SHR was not salt-sensitive, our findings (and those of others) have clearly demonstrated that these genetically hypertensive rats are, indeed, salt-sensitive. 12,13 Moreover, when desoxycorticosterone acetate was added to salt-loading, malignant hypertension developed. 12 Thus, in contrast with their normotensive Wistar-Kyoto (WKY) controls that responded to long-term salt-loading with increased cardiac output but unchanged arterial pressure, the SHR demonstrated increased arterial pressure and total peripheral resistance and a normal cardiac output (and, hence, a normal ventricular preload was associated with salt-loading).…”
Section: Personal Investigative and Other Supportive Evidencementioning
confidence: 99%
“…12,13 Moreover, when desoxycorticosterone acetate was added to salt-loading, malignant hypertension developed. 12 Thus, in contrast with their normotensive Wistar-Kyoto (WKY) controls that responded to long-term salt-loading with increased cardiac output but unchanged arterial pressure, the SHR demonstrated increased arterial pressure and total peripheral resistance and a normal cardiac output (and, hence, a normal ventricular preload was associated with salt-loading). 13 We followed these reports with another study in which long-term low, normal, or 4% saltloading diets were administered to separate groups of SHR.…”
Section: Personal Investigative and Other Supportive Evidencementioning
confidence: 99%
“…exposed to high sodium intake over long periods of time aggravate their hypertension [2,[6][7][8]12] and they may even develop malignant hypertension [2,8,12]. These adverse effects of sodium on the arterial pressure of these rats are mediated through an elevation of peripheral vascular resistance [6,7], Tobian et al [27] have demonstrated that high sodium intake by the salt-sensitive Dahl rats resuited in reduction of prostaglandin concentration in their renal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…exposed to high sodium intake over long periods of time aggravate their hypertension [2,[6][7][8]12] and they may even develop malignant hypertension [2,8,12]. These adverse effects of sodium on the arterial pressure of these rats are mediated through an elevation of peripheral vascular resistance [6,7], Tobian et al [27] have demonstrated that high sodium intake by the salt-sensitive Dahl rats resuited in reduction of prostaglandin concentration in their renal tissue. The kidney is the major producer of E prostaglandins and these substances have been shown to play an important role in blood pressure regulation through local vasodilation and sodium excretion by the kidney [5,11,15,26], Dunn [9] has reported that the kidneys of SHR increase the production of all prostaglandins with time, possibly, in an attempt to arrest the progression of hypertension.…”
Section: Introductionmentioning
confidence: 99%